Twig-like MCA: A Rare Vascular Anomaly - Pant, Niharika; Rajbhandari, Saujanya; Rajbhandari, Suyasha; Ansari, Saddam; Raghubanshi, Nipun; Rajbhandari, Pravesh; Pant, Basant (Nepal Journal of Neuroscience, 2024)
Twig-like middle cerebral artery (T-MCA) or rete mirabile anomaly is a rare vascular anomaly with clinical relevance characterized by the replacement of the M1 segment by a plexiform network of small vessels. With an incidence ranging from 0.11% to 1.17%, it is more prevalent in Asia. The twig arises from the distal ICA and ends at the distal horizontal portion of MCA while lenticulostriate arteries (LSAs) arise from the plexiform network of the involved M1 segment. It is crucial to distinguish this embryological anomaly from Moyamoya Disease (MMD), moyamoya-like syndrome, atherosclerotic steno-occlusive disease, and vasculitis to prevent misdiagnosis and unnecessary treatment. We present the case of a 30-year-old male who complained of left eyelid ptosis and diplopia. Incidentally, he was diagnosed with both a twig-like middle cerebral artery (MCA) anomaly and an associated anterior communicating artery (ACoM) aneurysm. The twig-like middle cerebral artery (T-MCA) anomaly, also known as rete mirabile anomaly, is a rare vascular variation characterized by the replacement of the M1 segment with a plexiform network of small vessels. Here, we present a case of a 30-year-old male with left eyelid ptosis and diplopia, who was incidentally diagnosed with T-MCA anomaly along with an associated anterior communicating artery (ACoM) aneurysm.